Borneo and Sulawesi indigenous peoples, empires and area studies - Ooi, Keat Gin 1959- (Routledge studies in the modern history of Asia, 2020)
This book presents a great deal of new research findings on the history of Borneo, the history of Sulawesi and the interrelationship between the two islands. Some specific chapters focus on empires and colonizers, including the activities of James Brooke in Sulawesi, of Chinese mining communities in Borneo and of the the quisling issue in immediate post-war Sarawak. Other chapters consider indigenous peoples and how different regimes have handled them. The book is published in honour of Victor T. King, a leading scholar in the field of Southeast Asian studies, and a final chapter discusses his contribution to scholarship, in particular his views on how area studies should be approached, and the implications of this for future research.